Cognitive Behavioral Therapy in Cardiovascular Disease - Manolis, Theodora A.; Manolis, Antonis A.; Manolis, Antonis S. (Current Vascular Pharmacology, 2025)
Introduction/ObjectiveThe influence of cognitive behavioral therapy (CBT) and its modalities on various neuropsychiatric conditions is herein explored together with their impact on specific cardiovascular (CV) diseases (CVD).MethodsA comprehensive review of the literature was undertaken via the PubMed, Scopus and Google Scholar on the above relevant topics. The focus was on large randomized controlled trials and meta-analyses.ResultsAmong the various neuropsychiatric disorders, depression and anxiety commonly occur in CVD patients, frequently eluding clinician's attention. This reciprocal liaison may incur higher rates of morbidity/mortality, through physiological and behavioral mechanisms. Multimodal psychiatric interventions, using medications and psychotherapies, such as CBT, seem promising. Such mindfulness-based interventions have the potential to be an efficacious complementary strategy to address psychological stress in CVD patients. As the cost of CBT is relatively low, such a supportive approach for stress management provides high patient acceptability, with a positive impact on improving quality of life, by promoting CV health and mitigating CV complications.ConclusionThere is ample evidence of a reciprocal liaison between heart and mind. Several CV risk factors are strongly affected by diseases of the mind, and the clinical course of various CVDs is influenced by affective or other psychiatric disorders. CBT and relevant mindfulness-based interventions have a significant supportive role in patients with various CVDs by targeting CV risk factor(s) or the underlying specific CVD and by identifying and addressing psychosocial issues. In this direction, various CBT interventions can provide the means to favorably influence both CV risk factors and CVDs.
Keywords: emotional stress